Oxford Shakespeare : the Merchant of Venice. - Shakespeare, William (Oxford University Press, 1993)
This edition presents a fresh examination of the text and all the important aspects of its significance and meaning. Fully annotated, it also includes a selective collation of important variant readings and a general introduction that treats various topics.